Analysis of citizen science in Brazil: A study of the projects registered in the Civis platform - Witt, Amanda Santos; Silva, Fabiano Couto Corrêa da (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. In 2022, the Civis platform of the IBICT (Brazilian Institute for Information in Science and Technology) was created. It aimed to provide infrastructure and content for understanding and dissemintating the use of Citizen Science in Brazil. It also aimed to provide the basis for developing initiatives and methodologies in this area. This study analyses the implementation of citizen science in the context of open science. The study seeks to understand how the platform promotes the participation of society in various stages of the scientific process and not only in data collection. Research/Methodology/Approach. The citizen science projects available on Civis: Citizen Science Platform will be surveyed and analyzed. The data collected in October 2022 are subdivided into five main categories: (1) area, (2) data collection, (3) social participation, (4) open data, and (5) scope. These categories are relevant to understand the current stage of citizen science projects in the Brazilian scenario, including the most essential knowledge areas, data collection procedures, levels of openness and access to scientific data, and the territorial coverage of these projects. Results/Discussion. 24 citizen science projects were registered on the Civis platform, most of which are contributive. The primary area of emphasis is Biological Sciences and they use technological infrastructure for mobile data collection. Conclusions. Civis is a multidisciplinary platform to promote citizen science in Brazil. The registration of projects is voluntary, which may explain the low adhesion to the platform, besides its recent launch. Originality/Value. Civis is an essential first-approach tool that enables the understanding of citizen science in Brazil.